Immune Modulation by Inhibitors of the HO System - Fernández-Fierro, Ayleen (Int J Mol Sci, 2020)
The heme oxygenase (HO) system involves three isoforms of this enzyme, HO-1, HO-2, and HO-3. The three of them display the same catalytic activity, oxidating the heme group to produce biliverdin, ferrous iron, and carbon monoxide (CO). HO-1 is the isoform most widely studied in proinflammatory diseases because treatments that overexpress this enzyme promote the generation of anti-inflammatory products. However, neonatal jaundice (hyperbilirubinemia) derived from HO overexpression led to the development of inhibitors, such as those based on metaloproto- and meso-porphyrins inhibitors with competitive activity. Further, non-competitive inhibitors have also been identified, such as synthetic and natural imidazole-dioxolane-based, small synthetic molecules, inhibitors of the enzyme regulation pathway, and genetic engineering using iRNA or CRISPR cas9. Despite most of the applications of the HO inhibitors being related to metabolic diseases, the beneficial effects of these molecules in immune-mediated diseases have also emerged. Different medical implications, including cancer, Alzheimer´s disease, and infections, are discussed in this article and as to how the selective inhibition of HO isoforms may contribute to the treatment of these ailments.